Metacognition and Intersubjectivity: Reconsidering Their Relationship Following Advances From the Study of Persons With Psychosis - Hasson-Ohayon, Ilanit; Gumley, Andrew; McLeod, Hamish; Lysaker, Paul H. (Frontiers in Psychology, 2020)
As research on metacognition has progressed a significant array of definitions, methodologies and therapeutic applications have emerged. Some of this work has primarily framed metacognition as an activity carried out by one person in order to know, monitor and adjust their beliefs, memories and behaviors. Accordingly, problems with metacognition have often been characterized as issues related to cognition. This however risks neglecting how metacognition is also a fundamentally intersubjective act, one in which human beings know and reflect upon themselves and others primarily with and through connections with other people. In this paper we review research on metacognition in schizophrenia using the integrative model of metacognition and a research paradigm in which metacognition is assessed within personal narratives. Stimulated by this work we discuss how disturbances in intersubjective experience and metacognitive capacity mutually influence one another, with disruptions in metacognition perhaps more deeply understood as disruptions in relatedness with others. We then discuss how metacognition and intersubjectivity each affect mental health. We finally focus on the implications of this for treatments that target metacognition as well as future directions for research.